2022
DOI: 10.1088/1742-6596/2265/4/042011
|View full text |Cite
|
Sign up to set email alerts
|

Using The Helix Mixing Approach On Floating Offshore Wind Turbines

Abstract: In recent years dynamic induction control has shown great potential in reducing wake-to-turbine interaction by increasing the mixing in the wake. With these wake mixing methods the thrust force will vary in time. If applied to a floating offshore wind turbine, it will cause the platform to move. In this paper the effect of the Helix mixing approach on a DTU10MW turbine on the TripleSpar platform and its wake is evaluated. When the Helix mixing approach is applied at Strouhal equal to 0.25, the yaw movement is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In this case, the second turbine operated at its static optimum. The effect of the helix approach when applied to a floating wind turbine was investigated by van den Berg, de Tavernier & van Wingerden (2022). They observed that the helix incites significant yawing of the turbine, further aiding the wake recovery process.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the second turbine operated at its static optimum. The effect of the helix approach when applied to a floating wind turbine was investigated by van den Berg, de Tavernier & van Wingerden (2022). They observed that the helix incites significant yawing of the turbine, further aiding the wake recovery process.…”
Section: Introductionmentioning
confidence: 99%
“…Knowing the location of the breakdown provides insight into when the wake mixing process is triggered. QBlade has previously been used in [12,17,13] for a similar type of research. The settings described in [17] are also used in this work.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the Helix wake mixing method applies a time-varying tilt and yaw moment to the turbine that typically is of such magnitude that the motions remain small. However, semi-submersible type floaters such as the TripleSpar [11] have an eigenfrequency in yaw motion for which the excitation frequency falls within the frequency range with which the Helix is typically applied [12,13]. For a typical blade pitch input used for the Helix wake mixing method the resulting yaw motion can reach between 5 to 10 degrees for these type of platforms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since FOWTs are newer, the understanding and modeling of their wake characteristics is still in development. However, initial studies indicate that the wakes behind FOWTs may dissipate faster compared to wakes behind fixed-bottom wind turbines [29,30]. This suggests a potential advantage of floating offshore wind farms: Since utility-scale fixed-bottom wind farms can lose 10-20% of their energy production per year due to wake interactions between turbines [31], for the same layout as a fixedbottom wind farm in similar wind conditions, a floating wind farm may be able to produce significantly more energy by naturally mitigating wake interactions.…”
Section: Introductionmentioning
confidence: 99%